Comparative study of alternative biofuels on aircraft engine performance - Azami, Muhammad Hanafi; Savill, Mark (Sage Publications, 2017)
Aviation industries are vulnerable to the energy crisis and simultaneously posed environmental concerns. Proposed engine technology advancements could reduce the environmental impact and energy consumption. Substituting the source of jet fuel from fossil-based fuel to biomass-based fuel will help reduce emissions and minimize the energy crisis. The present paper addresses the analysis of aircraft engine performance in terms of thrust, fuel flow and specific fuel consumption at different mixing ratio percentages (20%, 40%, 50%, 60% and 80%) of alternative biofuel blends already used in flight test (Algae biofuel, Camelina biofuel and Jatropha biofuel) at different flight conditions. In-house computer software codes, PYTHIA and TURBOMATCH, were used for the analysis and modeling of a three-shaft high bypass-ratio engine which is similar to RB211-524. The engine model was verified and validated with open literature found in the test program of bio-synthetic paraffinic kerosene in commercial aircraft. The results indicated that lower heating value had a significant influence on thrust, fuel flow and specific fuel consumption at every flight condition and at all mixing ratio percentages. Wide lower heating value differences between two fuels give a large variation on the engine performances. Blended Kerosene–Jatropha biofuel and Kerosene–Camelina biofuel showed an improvement on gross thrust, net thrust, reduction of fuel flow and specific fuel consumption at every mixing ratio percentage and at different flight conditions. Moreover, the pure alternative of Jatropha biofuel and Camelina biofuel gave much better engine performances. This was not the case for the Kerosene–Algae blended biofuel. This study is a crucial step in understanding the influence of different blended alternative biofuels on the performance of aircraft engines.